THE EFFECTIVENESS OF E-GOVERNMENT THROUGH THE MLAKU DEWE (BMW) FILE IN MASANGAN WETAN VILLAGE, SUKODONO DISTRICT - Sabila, Nauly; Mursyidah, Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to evaluate the effectiveness of the implementation of e-government through the Mlaku Dewe (BMW) File application in Masangan Wetan Village, Sukodono District, as an effort to enhance the quality of public services in densely populated areas previously constrained by manual administrative systems. Method: A descriptive qualitative approach was employed, utilizing structured interviews and observations, with the analysis guided by Richard M. Steers’ theory of organizational effectiveness, which emphasizes goal achievement, integration, and adaptation. Results: Findings indicate that the BMW application significantly improves service efficiency by reducing processing time from 3–4 days to 1–2 hours, streamlining bureaucratic procedures, and enhancing public satisfaction. The system further facilitates multi-user access, online document tracking, and integration with local community structures such as RT/RW. Nevertheless, challenges persist, particularly regarding limited socialization efforts and the need to strengthen the technical capacity of village officials. Novelty: This research contributes by offering a unique analysis of e-government at the village level through the lens of organizational effectiveness theory, demonstrating that the BMW application serves as an innovative model for advancing digital governance in local contexts.